Strategy of the As SALAM Product Sustainability Using the Product Life Cycle Approach - Istianah Istianah; Dhoqi Dofiri; Muhammad Ahsan (Budapest International Research and Critics University, 2022)
This recent study aimed to see and then measure the dynamics of the As SALAM (the abbreviation of Nabung Saham Modal Sampah) products and the strategies needed to encourage the growth of entrepreneurship. This research methodology used an action research approach with an interpretation pattern to develop ideas through data collection, participant observation, interviews, and focused discussions. Data analysis was done using NVIVO12 Plus by utilizing the menus available in the launch of the program based on the matrix and word frequency models. It was found that advancing As SALAM products could be done by improving strategy formulation, to be sustainable using the Product Life Cycle approach as a process of measuring the position of As SALAM through four phases; introduction, growth, maturity, and decline. This formulation generates new power to develop As SALAM on a large scale with a more extended period. As a practical implication, this formula has two advantages; first, it can be used as a reference for future management of the As SALAM strategy to grow entrepreneurial embryos. Secondly, this strategy helps carry out the function of As SALAM as an educational medium for the public and provides a stimulus to develop the Islamic economy in utilizing digital technology, e-commerce, and investment based on sharia principles.